High Performance Liquid Chromatographic Determination of Solasodine in Solanum Species - Thongchai, W.; Liawruangrath, B.; Liawruangrath, S.; Saysin, S. (Asian Journal of Chemistry, 2011)
This study incorporates HPLC analysis of solasodine from Solanum indicum Linn. and Solanum trilobatum Linn. Solasodine was determined by HPLC using SphereClone 3μ ODS, 100 × 4.6 mm as an analytical column with the mobile phase 10 mM phosphate buffer-acetonitrile (75:25, v/v) adjusted to pH 3.0. The flow rate was adjusted to 1.0 mL min-1. The injection volume was adjusted to 50 μL and the absorption was made at 530 nm. Linear calibration curve was obtained over the concentration range of 2.5-60.0 μg mL-1 of solasodine with a correlation coefficient of 0.9980. The limit of detection (LOD) was found to be 0.13 μg mL-1. The limit of quantification (LOQ) value was found to be 0.43 μg mL-1. The RSD of the proposed method obtained by assaying six replicate injections of 10, 20 and 30 μg mL-1 of solasodine for intra-day and interday were found to be 1.8-2.4 and 1.0-2.8 %, respectively. The mean percentage recovery was found to be 97.23 ± 4.71 %. The proposed method was applied to the determination of solasodine in Solanum indicum Linn. and Solanum trilobatum Linn. in Solanaceae family. The mean contents of solasodine in Solanum indicum Linn. and Solanum trilobatum Linn. were found to be 0.48 and 1.32 mg g-1, respectively. The method has been applied to the determination of solasodine in various plant samples.